ZAKAT SEBAGAI KATALISATOR KEMANDIRIAN EKONOMI: PERAN STRATEGIS LAZISKAF - Nikma, Raudatun; Idil Ghufron, Moh. (Penerbit Lafadz Jaya, 2025)
This study aims to examine the role of zakat as a catalyst for improving economic independence in the community through management strategies implemented by the Zakat, Infaq, Shadaqah, and Waqf Management Institution (LAZISKAF) at Pondok Pesantren Nurul Jadid. Using a qualitative descriptive approach, the study employs a case study method, where data is gathered through in-depth interviews with zakat managers and beneficiaries, direct observation, and literature studies from relevant sources. Thematic analysis techniques are applied to identify zakat management patterns, assess the effectiveness of distribution, and evaluate its impact on the welfare of the mustahik. The findings show that LAZISKAF’s zakat management strategies, including accurate identification of mustahik, needs-based distribution, and the integration of technology in recording and fund distribution, play a significant role in enhancing the economic independence of beneficiaries. Economic empowerment programs and business capital assistance have proven to support mustahik in transitioning toward better economic independence. Furthermore, the implementation of a rotating zakat distribution system helps expand the reach of aid and increases the overall program’s effectiveness. Therefore, zakat plays a strategic role as an Islamic economic instrument, not only as social assistance but also as a tool for sustainable economic empowerment. Optimizing zakat management through transparency, accountability, and technological innovation is crucial for maximizing its impact on community welfare. Collaboration among stakeholders, including the government and society, is essential to strengthen a professional zakat management system focused on independence.